2007
DOI: 10.1002/ejic.200600917
|View full text |Cite
|
Sign up to set email alerts
|

[CuII4] Clusters From the Self‐Assembly of Two Imidazolidinyl 2‐Phenolate‐Bridged [CuII2] Units: The Role of the Chloride Bridge

Abstract: A new family of tetracopper clusters [Cu 4 have been synthesised and characterised. The X-ray crystal structure of 1a reveals that the template action of the spherical Cl -anion (µ 4 -Cl -), which features a unique rectangular planar bridging mode, is responsible for the self-assembly of two [Cu 2 L] + units in complex 1a. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…[7] We and others have been exploring the dinucleating properties of the ligand H 3 L (Scheme 1) {2-(2Ј-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-3-azabut-3-enyl]-1,3-imidazolidine} [8] and its close derivative H 3 LЈ {2-(2Ј-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-4-methyl-3-aza-on these templates before coordination with L 3- but-3-enyl]-2-methyl-1,3-imidazolidine} [9] for various reasons, including their importance in coordination chemistry, molecular magnetism, and catalysis. [9][10][11][12][13][14][15][16] Scheme 1. During the course of these investigations, we have observed that in certain conditions, complexation reactions with Mn III , Fe III , Co III , or Cu II led to the hydrolysis of the imidazolidine ring [17,18] and even the destruction of one of the imine linkages of the hexadentate proligand. [19] We have also investigated the hydrolysis of H 3 L as triggered by Co III and isolated the mononuclear complex resulting from the hydrolyzed ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[7] We and others have been exploring the dinucleating properties of the ligand H 3 L (Scheme 1) {2-(2Ј-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-3-azabut-3-enyl]-1,3-imidazolidine} [8] and its close derivative H 3 LЈ {2-(2Ј-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-4-methyl-3-aza-on these templates before coordination with L 3- but-3-enyl]-2-methyl-1,3-imidazolidine} [9] for various reasons, including their importance in coordination chemistry, molecular magnetism, and catalysis. [9][10][11][12][13][14][15][16] Scheme 1. During the course of these investigations, we have observed that in certain conditions, complexation reactions with Mn III , Fe III , Co III , or Cu II led to the hydrolysis of the imidazolidine ring [17,18] and even the destruction of one of the imine linkages of the hexadentate proligand. [19] We have also investigated the hydrolysis of H 3 L as triggered by Co III and isolated the mononuclear complex resulting from the hydrolyzed ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Anions such as Cl − , N 3 − , HO − or O 2− can instead interact through direct coordination with metal ions having at least one vacant coordination site and can function as coordinating nucleating groups for the newer metal-ligand assembly. [7][8][9][10] Thus synthetic coordination chemistry that facilitates controlled aggregation around these anions to generate polynuclear complexes is of great interest. Involvement of double hydroxido bridges for a tetranuclear Cu 4 assembly has been studied by us on a piperazine based ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu 2 complexes considered so far as models to study magnetic exchange interactions, [12][13][14] DNA binding and cleavage, 15 oxidation of catechols, 13,16,17 and act as hydrolytic agents for glycosides 18 can also be used as building motifs for the construction of newer tetra-and polynuclear assemblies. [19][20][21][22] In general, the assembly of two dinuclear units leads to four types of Cu 4 aggregates, namely tetrahedron, cubane, partial dicubane and stepped cubane. 9 We have shown that the O 2− anion can function as a nucleating group for Cu 4 (μ 4 -O) aggregate formation from the assembly of two Cu 2 units bound to different ligand systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Phenoxido-bridged dinuclear copper(II) complexes having vacant coordination sites on both the metal ions are useful building units for the construction of tetra-and polynuclear complexes. [4][5][6][7][8][9] In this context, the phenoxido-methoxido double bridged Cu 2 complexes are important for possible co-ligand driven controlled aggregation process. In coordinatively unsaturated condition, the ability of both the copper(II) ions to accept fourth and fifth coordinating groups from basal and apical sites leads to the association of the two such dimeric units.…”
Section: Introductionmentioning
confidence: 99%